Spatial-temporal clustering of cases in a COVID-19 outbreak in Guangzhou city - Qian ZHANG; Xu-guang CHEN; Jian-xiong HU (Editorial Office of Chinese Journal of Public Health, 2022)
Objective To explore spatial-temporal clustering of coronavirus disease 2019 (COVID-19) cases in an outbreak epidemic in Guangzhou city, Guangdong province and to provide evidences for developing COVID-19 prevention and control measures. MethodsThe data on 215 local COVID-19 cases reported in Guangzhou city from April 4 to May 2, 2020 were collected and the cases' demographics and spatial-temporal distribution were described statistically. Knox test was used to identify possible spatial-temporal clustering of the cases by given specific critical thresholds. The spatial thresholds for the distance between the two cases' residential address were set varying from 0 to 1000 meters (m) with an interval of 100 m; the temporal thresholds for the time interval between the two cases' incident time were set varying from 1 to 15 days with an interval of 1 day. The strength of clustering (S-value) and relative risk (RR) of clustering for each gender- and age-group-specific case pair were calculated to analyze temporal-spatial clustering of case pairs. ResultsThe S-value and RR of the COVID-19 case pairs decreased with the increment in pairs' spatial distance and time interval. The RR value was the highest for a pair with the nearest spatial distance under the interval time of 1 day. For a case pair with the time interval of 1 day, the RR was 2.4 when the spatial distance between the pair's two cases being 100 m, while the RR was only 1.2 when the spatial distance being 3 kilometers (km). For male-male pairs, the S-value was higher under the time interval of 1 - 5 days with a spatial distance less than 300 m; for female-female pairs, the S-value was higher under the time interval of 1 - 7 days with a spatial distance less than 400 m; and for male-female pairs, the S-value was higher under the time interval of 1 - 4 days with a spatial distance less than 500 m. A stronger trend of spatial-temporal clustering was observed among female-female case pairs than among male-male case pairs. For age-group-specific case pairs, the S-value of child-child pairs with the time interval of 1 day was significantly higher than that of other age-group pairs and the S-value of middle-aged-youth pairs was higher under the time interval of 1 - 5 days with a spatial distance of less than 300 m. ConclusionSpatial-temporal clustering with between gender and age group differences was observed among the COVID-19 cases of an outbreak epidemic in Guangzhou city.